Role of the DinB Homologs Rv1537 and Rv3056 in Mycobacterium tuberculosis - Kana, Bavesh D. (American Society for Microbiology (ASM), 2010)
The environment encountered by Mycobacterium tuberculosis during infection is genotoxic. Most bacteria tolerate DNA damage by engaging specialized DNA polymerases that catalyze translesion synthesis (TLS) across sites of damage. M. tuberculosis possesses two putative members of the DinB class of Y-family DNA polymerases, DinB1 (Rv1537) and DinB2 (Rv3056); however, their role in damage tolerance, mutagenesis, and survival is unknown. Here, both dinB1 and dinB2 are shown to be expressed in vitro in a growth phase-dependent manner, with dinB2 levels 12- to 40-fold higher than those of dinB1. Yeast two-hybrid analyses revealed that DinB1, but not DinB2, interacts with the β-clamp, consistent with its canonical C-terminal β-binding motif. However, knockout of dinB1, dinB2, or both had no effect on the susceptibility of M. tuberculosis to compounds that form N(2)-dG adducts and alkylating agents. Similarly, deletion of these genes individually or in combination did not affect the rate of spontaneous mutation to rifampin resistance or the spectrum of resistance-conferring rpoB mutations and had no impact on growth or survival in human or mouse macrophages or in mice. Moreover, neither gene conferred a mutator phenotype when expressed ectopically in Mycobacterium smegmatis. The lack of the effect of altering the complements or expression levels of dinB1 and/or dinB2 under conditions predicted to be phenotypically revealing suggests that the DinB homologs from M. tuberculosis do not behave like their counterparts from other organisms.